THE POTENTIAL OF PHYSICAL CULTURE AS ONE OF THE LEADING INCENTIVES PERSONAL DEVELOPMENT OF STUDENTS - Marina Vasilievna Katrenko; Nina Nikolaevna Trotsenko; Yulia Ivanovna Zhuravleva; Irina Sergeevna Busheneva (Вестник Северо-Кавказского федерального университета)
The article deals with the notion of «potential», defined opportunities for physical culture in the development of the personality of students by means of artpedagogics.